Economic Impacts of Artificial Reefs: Sarasota County, FL - John Stevely (EDIS, 2012)
Florida Sea Grant and UF researchers conducted a study on the economic benefits associated with artificial reef programs in a six-county region of southwest Florida, where they asked private boater and for-hire operators and clients about their artificial reef use during 2009. Results are summarized in one-page fact sheets.